Impact of AI on health: Diagnosis, treatment and prevention of diseases - Torres Villanueva, Marcelino (2026)
Our research seeks to facilitate the analysis of various bibliographic sources that explore the implementation of Artificial Intelligence (AI) in the health sector, with a special focus on the fight against diseases. To ensure a systematic and comprehensive review, we used the PRISMA methodological framework. Our search focused exclusively on articles found in SCOPUS. The results of our research revealed a clear trend towards the application of AI for the detection and diagnosis of different types of cancer. We also identified South Korea, China and Germany as leading countries in the research and application of AI in the health sector, with a large number of articles. Additionally, our analysis highlighted the critical role of AI tools, such as Machine Learning, in improving healthcare and health research. Our goal is to highlight the significant impact of AI in the healthcare sector and its great potential to transform the way healthcare is delivered in the future.